Geometrical and mechanical draping of composite fabric - Cherouat, Abdelhakim; Borouchaki, Houman; Billoët, Jean-Louis (European Journal of Computational Mechanics, 2005)
This paper presents an optimization based method for simulation of forming processes of woven fabric reinforced composites. Two approaches are proposed for the simulation of the forming of woven fabric: geometrical and mechanical. The geometrical approach is based on a fishnet model. It is well adapted to pre-dimensioning fabrics and to give a suitable quantification of the resulting flat patterns. The mechanical approach is based on a mesostructural model. It allows us to take into account the mechanical properties of prepreg fabric and the various dominating mode of deformation of woven fabrics during the forming process. Some numerical simulations of forming process are proposed and compared with the experimental results in order to demonstrate the efficiency of our approaches.